Geographic distribution and research progress of national key protected wild plants in Hubei Province - WEI Xinzeng1,2, PU Yunhai3, SHI Hongwen4, XIAO Zhiqiang5, JIANG Mingxi1,2* (Guangxi Zhiwu)
The updated List of National Key Protected Wild Plants(LNKPWP)was released by National Forestry and Grassland Administration and Ministry of Agriculture and Rural Affairs of China in September 2021. By integrating literature search, herbarium record, field investigation and expert consultation, we compiled the updated list, investigated the geographic distribution map, research progress, threatened status, and protection status of national key protected wild plants(NKPWP)in Hubei Province. The results are as follows:(1)There are 155 species on the LNKPWP in Hubei Province, of which 11 species are protected at Category I and 144 species are protected at Category Ⅱ.(2)Geographic distribution of NKPWP in Hubei Province is uneven and concentrated in West and Southwest Hubei, with Shennongjia and Lichuan have the greatest numbers of NKPWP.(3)The most studied species are the species with economic value, flagship species and regional representative species. In addition, more than a third of the species(55 species)are almost unstudied. The research of NKPWP in Hubei Province focused on genetic diversity, genetic structure, future distribution prediction under global change conditions, and phylogeography, etc.(4)According to the Red List of China Biodiversity — Volume of Higher Plants, the NKPWP in Hubei Province contain 9 critically endangered species, 30 endangered species, 41 vulnerable species and 19 near-threatened species. The main threatened factors are direct mining or logging, habitat degradation or loss, and species intrinsic factors.(5)Until now, 137(88.4%)species of NKPWP in Hubei Province are wholly or partially located in protected areas, and the remaining 18 species(11.6%)are completely located outside protected areas. A total of 93 species of NKPWP have been introduced and cultivated in Hubei Province, while the other 62 species have not been recorded under ex situ conservation. In addition, very few species have been reintroduced into the wild.(6)Up to now, although the distribution ranges of seven wild plants in Hubei Province(five of which are endemic to Hubei)are limited and they are negatively affected by internal causes and human interference, they have not been included in the LNKPWP. In addition, this study points out the knowledge gaps in the research and protection of NKPWP in Hubei Province, and puts forward specific research suggestions and protection strategies.